Housing Affordability: Local and National Perspectives - Goodman, Laurie; Li, Wei; Zhu, Jun (International Journal of Population Data Science, 2018)
This paper presents a new approach to measuring affordable homeownership. Future changes in the homeownership rate will depend on the ability of today’s renters to become homeowners. Our proposed housing affordability for renters index (HARI) focuses on how affordable homeownership is for current renters. We look at the share of renters who reported the same or more income than those who recently purchased a home using a mortgage, in effect measuring how many renters have enough income to purchase a house. For each metropolitan statistical area (MSA), we construct a local area index that compares renters and borrowers in the same MSA and a national index that compares renters nationwide with homeowners in a specific MSA. We rely on the Administrative Data Research Facility to construct these indices. This database, constructed by the Urban Institute, aggregates American Community Survey variables and Home Mortgage Disclosure Act variables to common geographies. The new indices reveal that slightly more than a quarter of current US renters have incomes higher than those who recently became homeowners using a mortgage. The indices also reveal how housing affordability differs over time and across race/ethnicity groups and locations. We demonstrate the value of our new indices by showing that they are predictive of homeownership rates: MSAs that are deemed more affordable by our index have higher homeownership rates.